Dormancy and NKG2D system in brain metastases: Analysis of immunogenicity - Flüh, Charlotte (Int J Mol Med, 2020)
Patients with breast cancer (BC) and lung cancer (LC) are prone to developing brain metastases, which are associated with devastating prognoses. Dormant tumor cells, a population of non-apoptotic quiescent cells and immunological escape mechanisms, including the Natural Killer Group 2 member D (NKG2D) receptor-ligand system, represent potential mechanisms of tumor recurrence. To date, the immunological characteristics of dormant tumor cells concerning the NKG2D system in cerebral malignancies are mostly unknown. In the present study, an extensive characterization of dormant and NKG2D ligand (NKG2DL)(+) cells in cerebral metastases was performed. The expression profiles and localization patterns of various NKG2DL and several dormancy markers were analyzed in solid human brain metastases from patients with BC and LC using immunostaining and reverse transcription-quantitative polymerase chain reaction analyses. Statistical analysis was performed using Student's t-test and Bravais-Pearson correlation analysis. Not only 'peripheral', but also 'central' dormancy markers, which had been previously described in primary brain tumors, were identified in all cerebral metastases at detectable levels at protein and mRNA levels. Notably, the majority of NKG2DL(+) cells were also positive for 'central' dormancy markers, but not 'peripheral' dormancy markers in both patient groups. This cell population may represent a promising future therapeutic target.